2016
DOI: 10.1186/s11671-016-1503-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Visible-Light-Responsive Cu and N-Codoped AC/TiO2 Photocatalyst Through Microwave Irradiation

Abstract: N–Cu-activated carbon (AC)/TiO2 nanoparticles were prepared by the sol-gel technique through microwave irradiation to modify the visible-light response of TiO2. Their structure, surface chemical composition, and optical absorption properties were characterized. The results showed that the codoped particles had a higher surface area and smaller particle size than pure AC/TiO2 and monodoped AC/TiO2. X-ray photoelectron spectroscopy of N–Cu-AC/TiO2 showed that Cu atoms replaced Ti atom sites, whereas N atoms occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Figure 4b shows the spectrum of Ti ion, and its two peaks that located at 464.3 and 458.4 eV are attributed to Ti 2p 1/2 and Ti 2p 3/2 , respectively. This result implies that Ti exists as Ti 4+ from anatase-phase TiO 2 (Tian et al, 2016). Figure 4c shows the Ca 2p XPS spectrum.…”
Section: Characterization Resultsmentioning
confidence: 86%
“…Figure 4b shows the spectrum of Ti ion, and its two peaks that located at 464.3 and 458.4 eV are attributed to Ti 2p 1/2 and Ti 2p 3/2 , respectively. This result implies that Ti exists as Ti 4+ from anatase-phase TiO 2 (Tian et al, 2016). Figure 4c shows the Ca 2p XPS spectrum.…”
Section: Characterization Resultsmentioning
confidence: 86%
“…This result might be ascribed to the segregation of Cu-dopants which formed Cu-O-Ti bonds with TiO 2 and hindered the grain growth by blocking direct contact of TiO 2 grains. 11 Besides, the crystal size of TiO 2 in N-TDHG is smaller than that in TDHG, implying that the N-dopant also showed similar hindering effect. This might be explained by the fact that, when N-dopant was introduced to the TiO 2 lattice via the wet method (sol-gel method or hydrolysis method), it located at the interstitial sites and inhibited the crystal growth of TiO 2 grains.…”
Section: Characterization Resultsmentioning
confidence: 97%
“…This result is in accordance with other results in the literature, that is, the dopant Cu 2+ ion might have been transformed to Cu + and thus acted as electron acceptor, inhibiting the recombination of photo-induced electron and hole, leading to the improvement of photoactivity. 27 However, when the doping amount of Cu surpassed a certain value, its role changed to recombination center for both radicals, 11 which resulted in the decrease of photoactivity. In this work, this value was determined to be the doping percentage in CN-TDHG-2.…”
Section: Characterization Resultsmentioning
confidence: 99%
“…Wu et al found that the photocatalytic activities of monodoped TiO 2 -AC were signicantly improved by N/La co-doping and N/Cu co-doping, respectively. 17,18 However, few studies have focused on the study of AC modied with Ag and N co-doped TiO 2 (Ag-N-TiO 2 ).…”
Section: Introductionmentioning
confidence: 99%